Seneca's Scientific Fictions: Models as Fictions in the Natural Questions. (28th July 2014) - Roby, Courtney Ann
Abstract Seneca's Naturales Quaestiones explains the causes and functional mechanisms of natural phenomena, from common sights like rainbows to exotically out-of-reach ones like comets. The vividness with which he brings them all within the reader's grasp is certainly a literary feat as much as a scientific one, but the rhetorical power of his explanations does not cost them their epistemological validity. Analyses drawn from current philosophy of science reveal elements of fictionality omnipresent in scientific models and experiments, suggesting an approach to Seneca's 'scientific fictions' not as failed analogies but as a sophisticated expansion of the tradition of analogical scientific explanation.